Entrepreneurship Education and Entrepreneurial Attitudes as Predictors of Student Entrepreneurial Intention - Han Tantri Hardini; Mohammad Taufiq (Institute of Computer Science (IOCS), 2021)
This study aims to examine the effect of: (1). Entrepreneurship education on entrepreneurial intentions of students at the Faculty of Economics, Universitas Negeri Surabaya, (2). Entrepreneurial attitudes towards entrepreneurial intentions of students at the Faculty of Economics, Universitas Negeri Surabaya, and (3.) the simultaneous influence between entrepreneurship education and entrepreneurial attitudes on entrepreneurial intentions of students at the Faculty of Economics, Universitas Negeri Surabaya. The sample is students who take Entrepreneurship Education and already have a business, amounting to 90 students. Data were collected by means of a research questionnaire. The results showed that there was an effect of entrepreneurship education as evidenced by the value of t-count> t-table (4.300> 1.66256), with sig 0.00 <0.05, entrepreneurial attitudes towards entrepreneurial intentions as evidenced by the value of t-count> t-table (3.808> 1.66256), with sig 0.00 <0.05. Simultaneously the results of this study indicate the influence between entrepreneurship education and entrepreneurial attitudes on the entrepreneurial intentions of students at the Faculty of Economics, Universitas Negeri Surabaya as evidenced by the value of Fcount> Ftable (19.624> 3.10) with sig 0.00 <0.05.